(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
Competition among companies, due to their eagerness to corner the market, generates fluctuations that are perceived in the global economy and social development, this research work focuses its objective on analyzing social responsibility in small and medium-sized companies in the city of Guayaquil, methodologically a mixed approach was used that involves the different stakeholders, being the economic results a strategy of the company, demonstrating consistency in the behavior of social responsibility. It is concluded that the responsibility generated from small and medium enterprises in Ecuador seeks to generate an impact that modifies social conditions from the territory where they are located, in addition to the set of provisions that exist in the country to manage this type of corporate social responsibility.